2021
DOI: 10.3390/ijms23010030
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Therapy of Heart Failure: Is There a Future for B Vitamins?

Abstract: Heart failure (HF) is a plague of the aging population in industrialized countries that continues to cause many deaths despite intensive research into more effective treatments. Although the therapeutic arsenal to face heart failure has been expanding, the relatively short life expectancy of HF patients is pushing towards novel therapeutic strategies. Heart failure is associated with drastic metabolic disorders, including severe myocardial mitochondrial dysfunction and systemic nutrient deprivation secondary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 231 publications
(294 reference statements)
0
21
0
Order By: Relevance
“…First, vitamin B plays an important role in energy metabolism [ 4 , 30 ], and its deficiency may impair energy metabolism and stimulate fat production, and lead to obesity. A study found that vitamin B also appears to improve metabolism [ 31 ]. Second, vitamin B has antioxidant and anti-inflammatory effects [ 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, vitamin B plays an important role in energy metabolism [ 4 , 30 ], and its deficiency may impair energy metabolism and stimulate fat production, and lead to obesity. A study found that vitamin B also appears to improve metabolism [ 31 ]. Second, vitamin B has antioxidant and anti-inflammatory effects [ 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our findings revealed that both vitamin B1 and B5 levels were elevated in the LV muscle tissue of TASK −/− mice. B vitamins are precursors of essential coenzymes that play an essential role in energy metabolism ( Piquereau et al, 2021 ). Despite vitamin B5 (pantothenic acid) being vital for CoA biosynthesis, and consequently for metabolism, research on B5 deficiency and supplementation in the context of heart disease is scarce ( Piquereau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…B vitamins are precursors of essential coenzymes that play an essential role in energy metabolism ( Piquereau et al, 2021 ). Despite vitamin B5 (pantothenic acid) being vital for CoA biosynthesis, and consequently for metabolism, research on B5 deficiency and supplementation in the context of heart disease is scarce ( Piquereau et al, 2021 ). Several animal studies have reported that B5 has a cardioprotective effect due to its antioxidant properties ( Piquereau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, vitamins from the B complex (thiamine-vitamin B1; riboflavin-vitamin B2; niacinvitamin B3) are important cofactors in biochemical reactions, being essential for normal body growth and development, healthy skin, proper function of nerves and the heart, and red blood cell formation. Vitamins Bs are directly involved in energy metabolism and there is a recent interest in their role in the prevention of heart failure since there is a deficiency in vitamin B in patients affected by this clinical condition [53].…”
Section: Vitaminsmentioning
confidence: 99%